Induction of anoestrus in free-ranging African elephant (Loxodonta africana) cows using a gonadotrophin-releasing hormone vaccine - Schulman, Martin L. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.